The Babadook and the haunted space between high and low genres in the Australian horror tradition. Issue 1 (2nd January 2017) - Balanzategui, Jessica
ABSTRACT: The horror genre is a particularly fraught category in academic and mainstream critical discourse about Australian film genres. Australian horror films are often framed as either 'Australian Gothic' or 'Ozploitation, ' terms that prioritise issues of national identity, class and taste rather than genre. The oppositional relationship of these terms presents an obstacle to the widespread acceptance – both scholarly and popular – of local horror films. This is illuminated by a comparison of two recent Australian horror releases and their domestic receptions, Wolf Creek 2 (McLean, Greg. 2014. Wolf Creek 2 . Film. Adelaide: Duo Art Productions and Emu Creek Pictures) and The Babadook (Kent, Jennifer. 2014. The Babadook . Blu-Ray DVD. Melbourne: Umbrella Entertainment). Wolf Creek 2 was one of the most lucrative Australian films of 2014, however it was critically panned in large part due to its perceived commercialism and low-genre status. By contrast, The Babadook was the most critically praised Australian film of 2014, however the film received a limited domestic release. This paper explores how both The Babadook 's meagre domestic release and its near-universal critical praise can be related to its association with the high-art Australian Gothic tradition. Yet the film unsettles firmly entrenched art/genre, nationalism/commercialism dichotomies.